2022
DOI: 10.1002/ece3.8456
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus macaques compensate for reproductive delay following ecological adversity early in life

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 65 publications
3
25
0
Order By: Relevance
“…Prior evidence show that hurricanes affect negatively the dynamics of animal populations mainly through changes in food and habitat structure (Klinger, 2006;Pavelka & Behie, 2005;Woolbright, 1991), but few studies have shown the long-term effects on fertility and mortality (Luevano et al, 2022;Morcillo et al, 2020;Pavelka et al, 2007). The effects of hurricanes on the population dynamics of Cayo Santiago rhesus macaques are mostly driven by reductions in mean annual fertility, suggesting that survival is maintained at the expense of reproduction (Morcillo et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior evidence show that hurricanes affect negatively the dynamics of animal populations mainly through changes in food and habitat structure (Klinger, 2006;Pavelka & Behie, 2005;Woolbright, 1991), but few studies have shown the long-term effects on fertility and mortality (Luevano et al, 2022;Morcillo et al, 2020;Pavelka et al, 2007). The effects of hurricanes on the population dynamics of Cayo Santiago rhesus macaques are mostly driven by reductions in mean annual fertility, suggesting that survival is maintained at the expense of reproduction (Morcillo et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although food provisioning -and thus census taking -was resumed between 1 to 3 days after each hurricane (Morcillo et al, 2020), there is evidence of significant hurricane effects on several aspects of the population. Each hurricane caused 60-90% of canopy loss immediately after the event (Morcillo et al, 2020), and changes in the social structure (Testard et al, 2021), adverse demographic effects such as suppressed fertility (Luevano et al, 2022;Morcillo et al, 2020), as well as alterations in immune cell gene regulation (Watowich et al, 2022) associated to hurricanes have been reported.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, female macaques on Cayo Santiago that experienced hurricanes had a delayed reproductive start (i.e., later age at first birth). However, females appeared to compensate for this delay by producing more offspring during their prime reproductive years compared to females who did not experience a hurricane (Luevano et al, 2022). The natural disaster-related changes in reproductive biology may lead or be linked to modified aging trajectories which have yet to be explored.…”
Section: Ecological Modifiers Of Agingmentioning
confidence: 99%
“…The abundant amount of feed can affect the reproductive success of long-tailed macaques, thus causing the birth of individuals more quickly [7]. However, on the other hand, macaques also have a high survival rate, even being able to compensate for the ecological pressures in the form of an increased reproduction rate [27]. Mount Merapi National Park is a nature conservation forest with an original ecosystem.…”
Section: Introductionmentioning
confidence: 99%